Lightweight topology optimization with consideration of the fail-safe design principle for continuum structures. Issue 1 (2nd January 2021) - Peng, Xirong; Sui, Yunkang
ABSTRACT: The topology optimization of continuum structures is investigated to obtain an optimized topology satisfying the fail-safe design principle with suitable redundancy components. An optimization model with a nonlinear objective and linear constraints is established by defining the reciprocal topology variable as design variables and linearly approximating the structural performance. The model is solved by a dual sequential quadratic programming (DSQP) algorithm. Topology optimization with displacement constraints is used as an example. The presented optimization model and solution approach offers the following advantages. (1) A volume constraint, which makes determining reasonable values difficult, need not be specified. (2) Weighted coefficients, which combine multiple compliances under different load cases into a combined compliance, need not be specified as well. (3) The presented optimization model is a type of single-objective programming and thus avoids the challenges in the min-max model. (4) The proposed method shows a strong capability of finding optimum solutions.